Effects of Gemcitabine and Oxaliplatin Combined with Apatinib on Immune Function and Levels of SIL-2R and sicAM-1 in Patients with Gallbladder Cancer. (25th August 2022) - Qu, Linlin; Li, Kun; Liu, Kui; Hu, Weiyu
Abstract : Objective . The aim of this study was to determine how gemcitabine, oxaliplatin combination, and apatinib affect immune function and SIL-2R and sicAM-1 levels in patients with gallbladder cancer. Methods . Retrospective analysis of 116 patients with gallbladder cancer treated at our institution between February 2019 and February 2021. The patients were randomly divided into control and study groups, with 58 patients in each group. The study group received the combination of apatinib and the control group received gemcitabine and oxaliplatin. Immune function, serum tumor markers, short-term efficacy, survival measures, and incidence of adverse events were monitored and compared between the two groups. Results . CD3+, CD4+, CD4+/CD8+, and NK levels were significantly higher in both groups after treatment, while CD8+ levels were significantly lower; levels of sicAM-1, sicAM-1 (VEGF), and CEA were greatly reduced in both groups after treatment; there were significant differences between the study and control groups in terms of rr46.55% and DCR84.48%; at one year after treatment, the survival rate in the study group increased from 67.24% in the control group to 79.31%, with an increase in both PFs and 0S. Compared with the control group, the incidence of hypertension and myelosuppression, neutropenia, proteinuria, and hand-foot syndrome were lower in the study group (P < 0.05 ). All differences were statistically significant. Conclusion . In the treatment of gallbladder cancer, the use of gemcitabine and oxaliplatin combined with apatinib can effectively control the progression of patients' disease.